Exploring the effect of intracellular loop 1 genetic variants in human ABCG2 on transport activity and protein abundance - Sjöstedt, Noora; Timmermans, Ritchie G.M.; Vieraankivi, Marika; Suominen, Laura; Vellonen, Kati-Sisko; Bhattacharya, Madhushree; Auriola, Seppo; Kidron, Heidi (Drug metabolism and pharmacokinetics, 2025)
ABCG2 (breast cancer resistance protein, BCRP), can affect drug disposition, and thus, variation in the ABCG2 gene may alter drug exposure. We studied non-synonymous naturally occurring single-nucleotide variants (SNVs) in intracellular loop 1 (ICL1), which contains a coupling helix that transmits conformational changes in the protein. Reference ABCG2, the common SNVs V12M and Q141K, and five SNVs (K453R, I456V, H457R, G462R and G462V) in ICL1 were expressed in HEK293 cells. Additionally, combinations of selected SNVs were expressed to determine if an activating substitution in ICL1 could compensate for an inactivating substitution elsewhere. Transport of Lucifer yellow, estrone sulfate and rosuvastatin was studied using membrane vesicles and the ABCG2 abundance was quantified. While K453R and I456V abundance was similar to the reference ABCG2, abundance was lower for H457R and G462R/V. Apparent transport activities were partially substrate dependent, but excluding G462R/V, the ICL variants transported at least one of the substrates similarly to the reference ABCG2. In double substitutions, I456V had a more consistent effect than H457R on both transport activity and protein abundance. Altogether, SNVs in ICL1 can have both detrimental and beneficial effects on ABCG2 activity. Effects may be hard to predict, especially if more than one SNV is present. [Display omitted]